The unstable plaque - Hennerici, Michael G. (Cerebrovascular diseases, 2004)
Ischaemic strokes and transient ischaemic attacks are commonly caused by cerebral embolism originating from formation of a platelet-rich thrombus superimposed on an atherosclerotic plaque or by atherothrombotic plaque rupture in a carotid or intracranial artery. Despite advances made through ultrasound imaging in our understanding of atherosclerotic plaque progression and regression, the issue of whether differences in plaque structure alone can distinguish between lesions that become symptomatic and others that remain clinically silent continues to be debated. Recent biochemical and imaging studies have identified characteristics that may reflect a high risk of vulnerability, such as outward, abluminal plaque remodelling, the presence of intra-plaque haemorrhage, inflammation, severe flow disturbances around the encroaching lesion, plaque cap thinning and ulceration, and abnormal plaque motion. Plaque stability may be improved through management of traditional cardiovascular risk factors or with biological or pharmacological agents that target pathways involved in plaque pathophysiology. Unstable plaques place patients at risk of unpredictable ischaemic events and in patients with such lesions, specific preventive treatment beyond long-term antiplatelet therapy can be used to prevent new or recurrent events.